A community of practice pilot project for delivering early intervention professional development - Sanna Harjusola-Webb; Ashley Lyons; Michelle Gatmaitan (Social Welfare: Interdisciplinary Approach)
To ensure the fidelity of implementation of early intervention (EI) services in natural environments (NE), new types of partnerships are needed to systematically address this challenge. This paper describes one approach for effective professional development (PD) in EI to address the lack of systematic supports and PD for EI providers working with families in EI. The Early Intervention in Natural Environments Community of Practice (CoP) project was a six month study that endeavored to support previously trained EI providers in refining the use of their everyday practices. Given the potential of this approach for improving practices and child/family outcomes in the USA as well as in Europe through the development, implementation, and sustainability of a comprehensive system of ongoing PD, the NE CoP program evaluation plan and preliminary results are shared in their entirety.